Bronisław Piotr Piłsudski (1866-1918): Museum and Collections - Wawrzak, Małgorzata (Uniwersytet Mikołaja Kopernika w Toruniu, 2025)
Bronisław Piotr Piłsudski, Polish exile, linguist, meteorologist, ethnologist, folklorist,anthropologist, social activist, documentary photographer, publicist, economist, creator of folkloric and ethnographic collections, museologist. His complicated biography and multi-faceted research activity for years has been of interest to specialists from various fields. Museology and collecting are the core of his most important achievements. He is known mainly for his activities on behalf of the Tatra Museum and as the author of the first “model ethnographic museum” in Poland. Exiled for his participation in the attempted assassination of Tsar Alexander III (March 1, 1887), he spent almost 20 years in the eastern reaches of Russia, mainly in Sakhalin. His work for museums in Khabarovsk, Alexandrovsk and Vladivostok and gathering collections for museums in St. Petersburg, resulted in the development of a method of museum organization and collecting materials and intangible traces of the culture of the indigenous inhabitants of those areas. He became not only an observer and researcher but, above all, a spokesman and defender of the rights of denationalizedethnic minorities, mainly Nivkhs (Gilaks) and Ainu. After returning to the country, the experiences gained in exile became the basis for his activities in Podhale. In Zakopane he established the Ethnological Section and collected materials for the new “Rocznik Podhalański” magazine. He reorganized and expanded the Tatra Museum’s collections Laying the foundations for its collecting, scientific and publishing activities. Bronisław Piotr Piłsudski to polski zesłaniec, językoznawca, meteorolog, etnolog, folklorysta, antropolog, społecznik, fotograf-dokumentalista, publicysta, ekonomista,twórca folklorystycznych i etnograficznych kolekcji, muzeolog. Jego skomplikowanyżyciorys i wieloaspektowa aktywność badawcza od lat budzą zainteresowanie specjalistów z różnych dziedzin nauki. Problematyka muzealna i kolekcjonerska stanowi jeden z ważniejszych elementów jego dokonań. ...